Association between Cardiovascular Drugs and Chronic Kidney Disease in Non‐Institutionalized Elderly Patients. Issue 2 (3rd February 2015) - Becquemont, Laurent; Bauduceau, Bernard; Benattar‐Zibi, Linda; Berrut, Gilles; Bertin, Philippe; Bucher, Sophie; Corruble, Emmanuelle; Danchin, Nicolas; al‐Salameh, Abdallah; Derumeaux, Geneviève; Doucet, Jean; Falissard, Bruno; et al.
Abstract: Concern about the renal safety of commonly used cardiovascular drugs with demonstrated clinical benefit appears to be an obstacle to their use in the elderly. The objective was to describe the relationship between cardiovascular drugs and chronic kidney disease (CKD) in elderly individuals in the real‐life setting. This is an ancillary study of the prospective non‐interventional S.AGE (aged individuals) cohort. General physicians were free to prescribe any drug their patients needed. The participants were non‐institutionalized patients aged 65 years and older treated by their primary physician for either chronic pain or atrial fibrillation or type 2 diabetes mellitus. The estimated glomerular filtration rate (eGFR) derived from the CKD‐EPI formula was determined at inclusion and every year during 2 years of follow‐up. This study comprised 2505 patients aged 77.8 ± 6.2 years. At inclusion, the factors associated with CKD (eGFR < 60 ml/min/1.73 m 2 ) in multivariate analysis were age, female gender, hypertension, heart failure, history of atherothrombotic disease and renin angiotensin system blockers, loop diuretics and calcium channel inhibitors. Introduction of each of these three drug classes during the follow‐up period led to only a small decrease in the eGFR: −3.8 ± 12.7 ( p < 0.0006), −2.2 ± 12.0 ( p < 0.003) and −1.0 ± 13.4 ml/min./1.73 m 2 (NS), respectively. Only the introduction of loop diuretics was associated with CKD (OR 1.91, 95% CI: 1.25–2.90; p = 0.002). Renal safety of cardiovascular drugs in the elderly appears acceptable and should not be a barrier to their use.